2002
DOI: 10.1007/s00424-002-0925-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cholecystokinin receptor in the inhibition of gastric emptying by oxytocin in male rats

Abstract: The effects of oxytocin (OT) on gastric emptying and plasma levels of cholecystokinin (CCK) were studied in male rats. Gastrointestinal motility was assessed in rats 15 min after intragastric instillation of a test meal containing charcoal and Na2(51)CrO4. Gastric emptying was determined by measuring the amount of radiolabeled chromium contained in the small intestine as a percentage of the initial amount received. Blood samples were collected for OT and CCK radioimmunoassay. After administration of OT (0.2-0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
44
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 53 publications
5
44
2
4
Order By: Relevance
“…The dose of devazepide chosen in the present study blocked the inhibitory actions of exogenously administered CCK-8 on splanchnic sympathetic nerve activity and CCK-sensitive RVLM neurons (39; present study). Furthermore, many investigators have demonstrated that similar doses of devazepide are capable of reversing the effects of endogenously released CCK on pancreatic enzyme secretion (23,33,34), vagal afferent nerve discharge (7,11,18), gastric emptying (51), and food intake (37), suggesting that the dose chosen in our study is likely to have been adequate.…”
Section: Discussionmentioning
confidence: 78%
“…The dose of devazepide chosen in the present study blocked the inhibitory actions of exogenously administered CCK-8 on splanchnic sympathetic nerve activity and CCK-sensitive RVLM neurons (39; present study). Furthermore, many investigators have demonstrated that similar doses of devazepide are capable of reversing the effects of endogenously released CCK on pancreatic enzyme secretion (23,33,34), vagal afferent nerve discharge (7,11,18), gastric emptying (51), and food intake (37), suggesting that the dose chosen in our study is likely to have been adequate.…”
Section: Discussionmentioning
confidence: 78%
“…In adipose tissue, for instance, OT stimulates in vitro synthesis of protein and glycogen and facilitates lipogenesis but suppresses lipolysis (Mirsky and Perisutti, 1961;Krahl, 1964;Muchmore et al, 1981). Furthermore, peripheral OT may favor satiety by stimulating CCK release (Wu et al, 2002) and by potentiating glucose-induced insulin secretion in vitro and in vivo (Altszuler and Hampshire, 1981;Knudtzon, 1983;Gao et al, 1991;VanderWeele, 1994). It is likely, therefore, that the combination of high GC levels with concomitant low levels of leptin during fasting favors the release of endocannabinoids in the PVN, reducing the excitation of both parvocellular and magnocellular OT neurons in response to inputs triggered by satiety factors, such as CCK.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more evidence has indicated that OT may play a role in regulation of the gastrointestinal (GI) functions such as motility, sensation (13,18), and immune response to inflammation (4,10). Exogenous OT influences the GI motility, although the reports are diverse because of the differences of species, methods, and area of the gut (18,24). It has been suggested that the effect of OT on GI motility might be physiological.…”
mentioning
confidence: 99%